Molecular genetic detection and differentiation of Xanthomonas oryzae pv. oryzicola, bacterial leaf streak agents of rice - M. L. Koroleva; S. A. Blinova; A. A. Shvartsev; V. E. Kurochkin; Ya. I. Alekseev (Вавиловский журнал генетики и селекции)
The genus Xanthomonas comprises phytopathogenic bacteria which infect about 400 host species, including a wide variety of economically important plants. Xanthomonas oryzae pv. oryzicola (Fang et al., 1957) Swings et al., 1990 is the causal agent of bacterial leaf streak (BLS) being one of the most destructive bacterial diseases of rice. BLS symptoms are very similar to those of bacterial blight caused by closely related Xanthomonas oryzae pv. oryzae. X. o. pv. oryzae and X. o. pv. oryzicola and often occur in rice f ields simultaneously, so separate leaves may show symptoms of both diseases. The quarantine status and high severity of the pathogen require a highly eff icient, fast and precise diagnostic method. We have developed an assay for Xanthomonas oryzae pv. oryzicola detection using real-time polymerase chain reaction (qPCR) and PCR amplicon sequencing. The DNA samples of X. o. pv. oryzae and X. o. pv. oryzicola were obtained from the collection of CIRM-CFBR (France). To evaluate the analytical sensitivity of the assay, a vector construct based on the pAL2-T plasmid was created through the insertion of X. o. pv. oryzicola target fragment (290 bp). Primers and a probe for qPCR were selected for the hpa1 gene site. They allowed identifying all the strains the sequences of which had been loaded in the GenBank NCBI Nucleotide database before November 11, 2021. The SeqX.o.all sequencing primers were selected for the hrp gene cluster sequence, namely for the nucleotide sequence encoding the Hpa1 protein, the sequencing of which allows for eff icient differentiation of X. oryzae species. The analytical specif icity of the system was tested using the DNAs of 53 closely related and accompanying microorganisms and comprised 100 % with no false-positive or false-negative results registered. The system’s analytical sensitivity was not less than 25 copies per PCR reaction. Its eff icacy has been conf irmed using f ive different qPCR detection systems from different manufacturers, so it can be recommended for diagnostic and screening studies.